2021
DOI: 10.1038/s41598-021-86328-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain networks underlying the processing of sound symbolism related to softness perception

Abstract: Unlike the assumption of modern linguistics, there is non-arbitrary association between sound and meaning in sound symbolic words. Neuroimaging studies have suggested the unique contribution of the superior temporal sulcus to the processing of sound symbolism. However, because these findings are limited to the mapping between sound symbolism and visually presented objects, the processing of sound symbolic information may also involve the sensory-modality dependent mechanisms. Here, we conducted a functional ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Thirty-two Japanese subjects (17 males and 15 females) were recruited from a previous study by Kitada et al (2021a) and performed the activity described here as a separate study. The mean age of the Japanese subjects was 23.3 years (Range = 18-35).…”
Section: Japanese Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-two Japanese subjects (17 males and 15 females) were recruited from a previous study by Kitada et al (2021a) and performed the activity described here as a separate study. The mean age of the Japanese subjects was 23.3 years (Range = 18-35).…”
Section: Japanese Subjectsmentioning
confidence: 99%
“…The present study investigated the ratings of 60 sound-symbolic stimuli, which had been previously employed in a functional MRI study of Japanese subjects (Kitada et al, 2021a). The stimuli consisted of 24 conventional Japanese sound-symbolic words (12 "hard"; 12 "soft"), 24 novel sound-symbolic pseudowords aligned with the Japanese patterns (12 "hard"; 12 "soft"), and 12 non-sound-symbolic pseudowords.…”
Section: Sound-symbolic Wordsmentioning
confidence: 99%
“…From a psychological point of view, sound symbolism has been conducting research on the sensory information recognized and perceived by people through specific sounds and their emotional meaning. Researchers have attempted to find emotional meanings by linking hearing with perception areas for various senses, such as sight [3,4], taste [5], smell [6], touch [7], and motion [8]. One of the most famous examples in the visual field, the "bouba/kiki effect" is a phenomenon in which people associate a round shape when they hear "bouba" and a pointed shape when they hear "kiki" [1].…”
Section: Introductionmentioning
confidence: 99%
“…Judging the size of visual objects during presentation of sound symbolically incongruent, relative to congruent, pseudowords led to greater activity in bilateral anterior cingulate cortex, the right anterior superior temporal gyrus, the left posterior middle temporal gyrus and the right lingual gyrus (Itagaki et al, 2019). Congruent tactile hard/soft stimuli and visually presented Japanese words that were sound-symbolic for hardness/softness, relative to incongruent stimulus pairs, led to activity in a number of areas including the anterior insula and medial superior frontal gyrus bilaterally; these regions also distinguished between congruent and incongruent stimuli on multivoxel pattern analyses (MVPA) (Kitada et al, 2021), however, the reported analyses did not explore whether individual stimuli could be distinguished.…”
Section: Introductionmentioning
confidence: 99%